2017
DOI: 10.1002/jmri.25638
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of T1 and T2 mapping to detect intramyocardial hemorrhage in reperfused ST‐segment elevation myocardial infarction (STEMI) patients

Abstract: PurposeTo investigate the performance of T 1 and T 2 mapping to detect intramyocardial hemorrhage (IMH) in ST‐segment elevation myocardial infarction (STEMI) patients treated by primary percutaneous coronary intervention (PPCI).Materials and MethodsFifty STEMI patients were prospectively recruited between August 2013 and July 2014 following informed consent. Forty‐eight patients completed a 1.5T cardiac magnetic resonance imaging (MRI) with native T 1, T 2, and T2* maps at 4 ± 2 days. Receiver operating chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
4
25
1
1
Order By: Relevance
“…The weighted mean T 2 * values at 1.5 T in myocardial infarction (MI) patients was 28.5 ± 6.8 ms and 34.7 ± 3.7 ms in controls [39][40][41][42][43][44][45][46][47][48][49] (Table 1, Fig. 2).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The weighted mean T 2 * values at 1.5 T in myocardial infarction (MI) patients was 28.5 ± 6.8 ms and 34.7 ± 3.7 ms in controls [39][40][41][42][43][44][45][46][47][48][49] (Table 1, Fig. 2).…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…A small study previously showed that the hypointense core on the T1 or T2 maps could provide an alternative method to detect intramyocardial hemorrhage in cases where T2* is not available or not interpretable (Figures 1 and 2) 39 and further studies are needed to confirm these findings.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…14 The breakdown products of hemoglobin within the myocardium can be detected as a hypo-intense core 39 within the MI zone on T2*-imaging or T2*-mapping (Figures 1 and 2). Of the two approaches, T2*-mapping has been shown to have greater sensitivity for detecting intramyocardial hemorrhage following STEMI when compared to T2-mapping (Table 1).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…This leads to a cascade of haemoglobin decay products in the no reflow region during the weeks following reperfusion, with various iron states affecting T 2 , estimated T 1 , and true T 1 [ 121 ]. Clearly this poses problems for T 1 mapping, and thus CMR studies should be timed appropriately after reperfusion therapy [ 122 ].…”
Section: Errors In Specific Clinical Applicationsmentioning
confidence: 99%